Social factor as an indicator for service excellence in facilities management services - Kasim, Rozilah; Umar, Muhammad Akilu; Martin, David (JARDCS, 2018)
Local council are faced with challenges of how to satisfy the local populace with efficient services. General environmental cleanliness and waste collection is part of the responsibilities of the local council. Daerah Pontian is a local council whose function cut across this domain. Due to incessant complaints on by the service users on the need for these services to be improved provides an avenue for empirical paper to investigate the nature of the problem. The social background of the service providers is an important element assessed and it is relationship with service delivery. This paper focuses on social factor and its contribution to excellent service delivery at Daerah Pontian local. The objective of the research tries to identify values to be gained by better designing the service around the true needs of the service user. The research found out a significant relationship between social factor and service delivery. The research discovered that customer loyalty, commitment and readiness to comply with local council regulations are part of values to be gained by the municipal council if it provides training and development, knowledge and skill. The limitation of this research is that it is only focused on the service provider assessment whether they provide an excellent service. Therefore, another area of research need to be carried out on the service user, to assess their complaints in relation to their background and services delivered in their area